2011
DOI: 10.1080/14735903.2011.603904
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impact of Bt cotton: findings from a case study in China using panel data

Abstract: Bt cotton has been cultivated in China for a decade. Studies have been conducted to assess theimpact on productivity and pesticide use. Limitations of these studies are the short time period considered and the reliability of data. This paper presents findings from monitoring 150 Bt cotton farmers in Shandong province in 2002 and 2005. Descriptive analysis reveals that pesticide use increased while seed price and Bt toxin concentration decreased. The Bt variable was consistently insignificant in the estimated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…In terms of the evolution of Bt cotton effectiveness and profit, 29.2 per cent of all farmers considered that there was a downward trend. As regards the general satisfaction reported in the early 2000s (Pray et al, 2002), but subsequently challenged (Pemsl, Volker, Wu, & Waibel, 2008), our results quantify the decline in the positive opinion of Bt cotton.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…In terms of the evolution of Bt cotton effectiveness and profit, 29.2 per cent of all farmers considered that there was a downward trend. As regards the general satisfaction reported in the early 2000s (Pray et al, 2002), but subsequently challenged (Pemsl, Volker, Wu, & Waibel, 2008), our results quantify the decline in the positive opinion of Bt cotton.…”
Section: Resultsmentioning
confidence: 53%
“…The use of Bt cotton was so quickly generalised that a comparison with non-Bt cotton has become difficult: farm holdings are somewhat too uniform to demonstrate any differentiation in performance. Nevertheless, Chinese farmers might have reason to question the real performance of Bt cotton, as it was found that all Bt cotton varieties used by farmers had low concentrations of Bt toxins, jeopardising their effectiveness in controlling pests (Pemsl, Voelker, Wu, & Waibel, 2011). Low concentrations of Bt toxins have also been observed in hybrids in YaRV (Xu, Fok, Bai, & Zhou, 2008).…”
Section: Marketing Of Bt Cotton Cultivars and Seedsmentioning
confidence: 98%
“…Moreover, these practices may induce outbreaks of other rice pests by disrupting natural enemy activity. Insecticides induce the outbreaks of secondary pest (Pemsl et al, 2011) and affect natural enemy abundances in fields (Dutcher, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Such occurrence of secondary pests would require additional spraying with conventional broad‐spectrum insecticides, which may erode (at least) some of the benefits of GEIR crop technology (Pemsl et al. ).…”
Section: Introductionmentioning
confidence: 99%